A Numerical Study of Railway Ballast Subjected to Direct Shearing Using the Discrete Element Method - Hongyi Zhao; Jing Chen (Advances in Materials Science and Engineering)
Railway ballast is a coarse granular material used to carry train loads and provide drainage for the rail tracks. This study presents numerical explorations of the mechanical performance of ballast aggregates subjected to direct shear tests. The discrete element method (DEM) was used to investigate the microscopic characteristics of ballast aggregates during shearing while considering contact distribution, particle rotation, and particle displacement. By testing the angle of repose of ballast aggregates, the parameters for the DEM contact model could be calibrated. Four specimens were prepared and then subjected to different normal pressures. The results show that the contact between ballast particles intensifies in terms of the amount and magnitude as the normal pressure increases. A Fourier analysis was applied to investigate the anisotropy of contact normal and the contact forces for ballast aggregates at different shearing phases. The rotational and translational movements of ballast particles were investigated, and this investigation revealed that particle rotation gradually increased as the shearing propagated. Four regions in the aggregates were identified according to the translational pattern of ballast particles. The results of this research provide an in-depth analysis of microscopic characteristics from a particulate scale.